Potential Medication Errors in Electronic Prescribing in A Primary Health Care - Nurfitria, Rizki Siti; Adillah Effendi , Rima Nur; Iskandar , Deni (Indonesian Journal of Pharmaceutical and Clinical Research, 2019)
An effort to reduce medication errors is to use drugs prescription electronically[1,2,4]. However, there needs to be an evaluation of this system, because this system is not free from errors in medication. This study aimed to find out the description of prescribing flow, to examine electronic prescription completeness, and find out the potential medication errors that occur in the prescribing phase of electronic prescription using prescribing indicators[1,5,9,10]. This study used observational method by taking general practice outpatient prescription data of March 2018 in a company health service located in Bandung and analyzed descriptively[6,7,8]. Electronic prescription of medicines at this health care was made and inputted by doctors. When an error occured on a computer system, the doctor would prescribe it manually so that the patient can still be served. Incompleteness of the most common recipe was on administrative requirements where all prescriptions did not listed the doctor's practice permit, patient's gender, patient's weight, telephone number of the place of practice, and patient's contact number. Medication errors had the most potential for the occurrence of prescription writing with two or more drugs interacting and this error was classified as category D according to The National Coordinating Council for Medication Error Reporting and Prevention (NCC-MERP).